Effectiveness of moving average rules during COVID-19 pandemic: evidence from Malaysian stock market - Lee, Kelvin Yong Ming; Mohamad Jais (Penerbit Universiti Kebangsaan Malaysia, 2021)
The COVID-19 outbreak significantly impacted the Malaysian stock market. To some extent, the Movement Control Order (MCO) implemented in the country affected the financial performance of listed companies. In consequence investors were quite uncertain of future movements of the stock market. Effective analysis techniques are thus required to study the market movements. Investors shall rely on signals emitted by technical indicators for their investment decisions making. The aim of this study is to examine the performance of the MA rules in Malaysian stock market during the different stages of the MCO. The sample used comprised 30 largest market capitalization stocks listed in the stock market. The period of study spanned 2 January 2020 to 30 August 2020. More than 50% of the buy signals emitted by (5,60,0.01) were found linked with positive returns in the next trading day during the MCO and CMCO sub-period respectively. Conversely, 41.28% and 34.78% of the sell signals emitted by (5,50,0.01) during the respective MCO and CMCO sub-period were linked with negative returns. Among all the MA rules, (5,60,0.01) generated the highest average return of 0.88% during the MCO and CMCO sub-period. Importantly, MA rules, (5,60,0.01) also generated positive returns during the out-of-sample period. The findings of this study shall contribute to the existing literature related to technical analysis. Besides that, the findings will benefit investors the most, inducing them to generate returns or avoid losses during the critical COVID-19 pandemic period. Investors are recommended to take the signals emitted by MA rules as alternative reference for their investments. Lastly, the relevant organizations should conduct more seminars to inform and enhance analytical skill of their clients, particularly retail investors.